Arnold Beckman receiving the Association of Clinical Scientists' diploma of honor (Arnold Beckman with a Association of Clinical Scientists award, 1982)
Arnold Beckman accepts the award from James Gadsden (right), president of the Association of Clinical Scientists. Joseph Ashley (left) was vice-president of Beckman's Health Care Products Organization. This award from the Association of Clinical Scientists "in recognition of sustained, salient, and meritorious contributions to clinical science and its professional advancement." A Beckman Instruments press release is attached to this image.
Keywords: Beckman, Arnold O.; Association of Clinical Scientists; Award presentations